High-strength foundation bolt and preparation method thereof

By using a combination of specific components and boron nitride reinforced phase in anchor bolts, the problem of insufficient mechanical properties of traditional anchor bolts is solved, which significantly improves its tensile strength and yield strength, extends service life and improves the tightening effect.

CN119800229AActive Publication Date: 2025-04-11HANDAN ZHAOYUN ELECTRIC FASTENER MFG CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510044434.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-11
Publication Date
2025-04-11
Estimated Expiration
2045-01-11

AI Technical Summary

Technical Problem

The mechanical properties of traditional anchor bolts are limited and are prone to break after being subjected to various loads for a long time, which reduces the service life and tightening effect of the bolts.

Method used

High-strength anchor bolts are used, and their base consists of components of a specific weight percentage, including C, Mn, V, W, Sn, Cu, Se, P and S. The rest is iron and its impurities, and boron nitride is introduced as the reinforcement phase. By optimizing components and modifying boron nitride, the mechanical properties of the bolts are improved.

Benefits of technology

The mechanical properties of anchor bolts are significantly improved, including tensile strength and yield strength, allowing them to withstand various loads more effectively, extend their service life and improve fastening effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of bolts, and provides a high-strength foundation bolt and a preparation method thereof.The foundation bolt comprises a base body and a reinforcing phase, and the base body is composed of, by weight, 0.2%-0.38% of C, 0.24%-0.35% of Mn, 0.12%-0.18% of V, 0.05%-0.15% of W, 0.14%-0.28% of Sn, 0.018%-0.15% of Cu, 0.018%-0.15% of Se, smaller than or equal to 0.055% of P, smaller than or equal to 0.045% of S and the balance iron and inevitable impurities; the reinforcing phase is boron nitride; the weight ratio of the matrix to the reinforcing phase is 100: (2-5). According to the technical scheme, the problem that the mechanical property of the foundation bolt is poor in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of bolts, and in particular to a high-strength anchor bolt and a preparation method thereof. Background Art

[0002] Anchor bolts are basic connectors that fix machinery and equipment or structures to the ground. They play a vital role in the fixation of building ancillary equipment and the overall stability of the building structure. For example, in high-rise buildings, elevator equipment is fixed to the building structure through anchor bolts. If there is a problem with the anchor bolts, the elevator may malfunction, affecting the normal use of the building. In addition, for some buildings with special requirements, such as earthquake-resistant buildings, anchor bolts can strengthen the connection between building equipment and the main structure, improve the seismic performance of the building in natural disasters such as earthquakes, and ensure the safety of people and property in the building. However, the mechanical properties of traditional anchor bolts are limited. Anchor bolts that bear various loads for a long time are easy to break, reducing the service life and tightening effect of the bolts. Therefore, improving the mechanical properties of anchor bolts is of great significance to improving the service life of anchor bolts. Summary of the invention

[0003] The invention provides a high-strength anchor bolt and a preparation method thereof, which solves the problem of poor mechanical properties of the anchor bolt in the related art.

[0004] The technical solution of the present invention is as follows: The present invention provides a high-strength anchor bolt, comprising a matrix and a reinforcement phase, wherein the matrix is ​​composed of the following components in weight percentage: C 0.2%-0.38%, Mn 0.24%-0.35%, V 0.12%-0.18%, W 0.05%-0.15%, Sn 0.14%-0.28%, Cu 0.018%-0.15%, Se 0.018%-0.15%, P≤0.055%, S≤0.045%, and the rest is iron and its inevitable impurities; The reinforcing phase is boron nitride; The weight ratio of the matrix to the reinforcement phase is 100:2-5.

[0005] As a further technical solution, the weight ratio of the sum of the weights of the Cu and the Se to the weight of the Sn is 1-3:3.

[0006] When the weight ratio of Cu and Se to Sn is 1~3:3, the mechanical properties of the anchor bolts can be further improved.

[0007] As a further technical solution, the weight ratio of the Cu to the Se is 1:1.

[0008] As a further technical solution, the median particle size of the boron nitride is 200nm~10μm.

[0009] As a further technical solution, the boron nitride is modified boron nitride, and the raw materials of the modified boron nitride include boron nitride, tungsten powder and molybdenum powder.

[0010] In the present invention, tungsten powder and molybdenum powder are used together to modify boron nitride, which can improve the chemical activity of boron nitride relative to molten metal, so that boron nitride has a better wetting effect on the molten metal, thereby further improving the interface bonding between boron nitride and the matrix, and further improving the mechanical properties of the anchor bolt.

[0011] As a further technical solution, the weight ratio of the boron nitride, tungsten powder and molybdenum powder is 90:2~4:1.

[0012] When the weight ratio of boron nitride, tungsten powder and molybdenum powder is 90:2~4:1, the mechanical properties of the anchor bolts are further improved.

[0013] As a further technical solution, the preparation method of the modified boron nitride comprises the following steps: mixing the boron nitride, the tungsten powder and the molybdenum powder, hot pressing and sintering, and crushing to obtain the modified boron nitride.

[0014] As a further technical solution, during the hot pressing sintering, the temperature is 1500-1600°C, the pressure is 15-25MPa, and the time is 2-3h.

[0015] As a further technical solution, the median particle size of the tungsten powder is 100-200 nm, and the median particle size of the molybdenum powder is 50 nm-200 nm.

[0016] The present invention also proposes a method for preparing the high-strength anchor bolt, comprising the following steps: S1, weighing materials according to the weight percentage of the matrix components, mixing, and melting to obtain molten steel; S2, adding the reinforcing phase to the molten steel, mixing evenly, casting, and molding to obtain a bolt blank; S3, the bolt blank is drawn, cold-forged, threaded and heat-treated, and then cooled to obtain the anchor bolt.

[0017] As a further technical solution, in step S3, during the heat treatment, the temperature is 650-850° C. and the time is 1-2 hours.

[0018] The working principle and beneficial effects of the present invention are: In the present invention, by optimizing the components of the matrix in the anchor bolt and introducing the boron nitride reinforcement phase, under the effective action of each component, a uniform and stable anchor bolt with good mechanical properties is prepared. Among them, by introducing three elements of Cu, Se and Sn, under the effective combination of the three, the mechanical properties of the anchor bolt are significantly improved. In addition, the boron nitride reinforcement phase is distributed in the anchor bolt, which can make the force of the anchor bolt uniform, thereby improving the overall bearing capacity of the anchor bolt and improving its mechanical properties. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] In the following embodiments and comparative examples, the Mn content in the ferromanganese alloy is 75wt%; the V content in the ferrovanadium alloy is 80wt%; the W content in the ferrotungsten powder is 70wt%; the Sn content in the tin-manganese alloy is 50wt%; the Cu content in the copper-iron alloy is 85wt%; the Fe content in the scrap steel is 97.3wt%; the Se content in the ferroselenium alloy is 52wt%; the median particle size of the tungsten powder is 150nm; the median particle size of the molybdenum powder is 100nm; and the median particle size of the boron nitride is 10μm.

[0021] Example 1 A high-strength anchor bolt comprises a matrix and a reinforcement phase in a weight ratio of 100:2, wherein the matrix is ​​composed of the following components in weight percentage: C 0.2%, Mn 0.24%, V 0.12%, W 0.05%, Sn 0.14%, Cu 0.018%, Se 0.018%, P 0.005%, S 0.005%, and the remainder is iron and its inevitable impurities; The reinforcement phase is boron nitride; The preparation method thereof comprises the following steps: S1, weighing, mixing and smelting ferromanganese alloy, ferrovanadium alloy, ferrotungsten powder, tin-manganese alloy, ferroselenium alloy, copper-iron alloy and scrap steel according to the weight percentage of the matrix to obtain molten steel; S2, adding boron nitride to the molten steel, mixing evenly, casting, and forming to obtain a bolt blank; S3. The bolt blank is drawn, cold-forged, threaded, heat-treated at 650°C for 2 hours, and cooled to obtain an anchor bolt.

[0022] Example 2 A high-strength anchor bolt comprises a matrix and a reinforcement phase in a weight ratio of 100:4, wherein the matrix is ​​composed of the following components in weight percentage: C 0.29%, Mn 0.3%, V 0.15%, W 0.1%, Sn 0.276%, Cu 0.042%, Se 0.042%, P 0.025%, S 0.025%, and the remainder is iron and its inevitable impurities; The reinforcement phase is boron nitride; The preparation method thereof comprises the following steps: S1, weighing the iron-manganese alloy, the vanadium-ferroalloy, the tungsten-iron powder, the tin-manganese alloy, the selenium-ferroalloy, the copper-iron alloy and the scrap steel according to the weight percentage of the matrix, mixing and smelting to obtain molten steel; S2, adding boron nitride to the molten steel, mixing evenly, casting, and forming to obtain a bolt blank; S3. The bolt blank is drawn, cold-forged, threaded, heat-treated at 750°C for 1.5h, and cooled to obtain an anchor bolt.

[0023] Example 3 A high-strength anchor bolt comprises a matrix and a reinforcement phase in a weight ratio of 100:5, wherein the matrix is ​​composed of the following components in weight percentage: C 0.38%, Mn 0.35%, V 0.18%, W 0.15%, Sn 0.28%, Cu 0.15%, Se 0.15%, P 0.055%, S 0.045%, and the remainder is iron and its inevitable impurities; The reinforcement phase is boron nitride; The preparation method thereof comprises the following steps: S1, weighing the iron-manganese alloy, the vanadium-ferroalloy, the tungsten-iron powder, the tin-manganese alloy, the selenium-ferroalloy, the copper-iron alloy and the scrap steel according to the weight percentage of the matrix, mixing and smelting to obtain molten steel; S2, adding boron nitride to the molten steel, mixing evenly, casting, and forming to obtain a bolt blank; S3. The bolt blank is drawn, cold-forged, threaded, heat-treated at 850°C for 1 hour, and cooled to obtain an anchor bolt.

[0024] Example 4 The only difference between this embodiment and embodiment 2 is that, in this embodiment, the weight percentage of Cu added is 0.1%, the weight percentage of Se added is 0.1%, and the weight percentage of Sn added is 0.16%.

[0025] Example 5 The only difference between this embodiment and embodiment 2 is that in this embodiment, the weight percentage of Cu added is 0.045%, the weight percentage of Se added is 0.045%, and the weight percentage of Sn added is 0.27%.

[0026] Example 6 The only difference between this embodiment and embodiment 2 is that in this embodiment, the weight percentage of Cu added is 0.09%, the weight percentage of Se added is 0.09%, and the weight percentage of Sn added is 0.18%.

[0027] Example 7 The only difference between this embodiment and embodiment 6 is that in this embodiment, the boron nitride is modified boron nitride, and its preparation method includes the following steps: 90 parts of boron nitride and 2 parts of tungsten powder are mixed, hot-pressed and sintered at 1500°C and 15MPa for 3h, and crushed to obtain modified boron nitride.

[0028] Example 8 The only difference between this embodiment and embodiment 6 is that in this embodiment, the boron nitride is modified boron nitride, and its preparation method includes the following steps: 90 parts of boron nitride and 2 parts of molybdenum powder are mixed, hot-pressed and sintered at 1600°C and 25MPa for 2h, and crushed to obtain modified boron nitride.

[0029] Example 9 The only difference between this embodiment and embodiment 6 is that in this embodiment, the boron nitride is modified boron nitride, and its preparation method includes the following steps: 90 parts of boron nitride, 1 part of tungsten powder and 1 part of molybdenum powder are mixed, hot-pressed and sintered at 1550°C and 20MPa for 2.5 hours, and crushed to obtain modified boron nitride.

[0030] Example 10 The only difference between this embodiment and embodiment 9 is that in this embodiment, 5 parts of tungsten powder are added.

[0031] Embodiment 11 The only difference between this embodiment and embodiment 9 is that in this embodiment, 2 parts of tungsten powder are added.

[0032] Example 12 The only difference between this embodiment and embodiment 9 is that in this embodiment, 4 parts of tungsten powder are added.

[0033] Comparative Example 1 The difference between this comparative example and Example 1 is that in this comparative example, Se is not added, the weight percentage of Cu added is 0.036%, and the weight percentage of Sn added is 0.14%.

[0034] Comparative Example 2 The only difference between this comparative example and Example 1 is that in this comparative example, no Cu is added, the weight percentage of Se added is 0.036%, and the weight percentage of Sn added is 0.14%.

[0035] Comparative Example 3 The difference between this comparative example and Example 1 is that in this comparative example, Cu and Se are not added, and the weight percentage of Sn added is 0.176%.

[0036] Comparative Example 4 The only difference between this comparative example and Example 1 is that in this comparative example, Sn is not added, the weight percentage of Cu added is 0.088%, and the weight percentage of Se added is 0.088%.

[0037] Comparative Example 5 The only difference between this comparative example and Example 1 is that in this comparative example, Cu, Se and Sn are not added.

[0038] Comparative Example 6 The only difference between this comparative example and Example 1 is that in this comparative example, no boron nitride reinforcement phase is added.

[0039] The anchor bolts prepared in Examples 1 to 12 and Comparative Examples 1 to 6 were tested for tensile strength and yield strength according to the test method in GB / T 228.1-2021 "Tensile test of metallic materials - Part 1: Room temperature test method", wherein the test speed was 0.004 s -1 , each group of test results is the average value of 5 samples.

[0040] Table 1 Mechanical properties test results of Examples 1 to 12 and Comparative Examples 1 to 6

[0041] Compared with Comparative Examples 1 to 5, the tensile strength and yield strength of Example 1 are significantly improved, indicating that when the three elements Cu, Se and Sn are introduced into the anchor bolt matrix, the three elements have a synergistic effect and can significantly improve the mechanical properties of the anchor bolt. Compared with Comparative Example 6, the tensile strength and yield strength of Example 1 are significantly improved, indicating that the addition of boron nitride reinforcement phase can also improve the mechanical properties of the anchor bolt.

[0042] Compared with Examples 2 and 4, the tensile strength and yield strength of Examples 5-6 are improved, indicating that when the weight percentage of Cu and Se to the weight ratio of Sn is 1-3:3, the mechanical properties of the anchor bolts can be further improved.

[0043] Compared with Examples 6 to 8, the tensile strength and yield strength of Examples 9 to 12 are improved, indicating that the mechanical properties of the anchor bolts can be further improved by modifying boron nitride with tungsten powder and molybdenum powder. Among them, compared with Examples 9 to 10, the tensile strength and yield strength of Examples 11 to 12 are improved, and when the weight ratio of boron nitride, tungsten powder and molybdenum powder is 90:2 to 4:1, the mechanical properties of the anchor bolts are further improved.

[0044] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-strength anchor bolt, comprising a matrix and a reinforcement phase, characterized in that: The matrix is ​​composed of the following components in weight percentage: C 0.2%-0.38%, Mn 0.24%-0.35%, V 0.12%-0.18%, W 0.05%-0.15%, Sn 0.14%-0.28%, Cu 0.018%-0.15%, Se 0.018%-0.15%, P≤0.055%, S≤0.045%, and the rest is iron and its inevitable impurities; The reinforcing phase is boron nitride; The weight ratio of the matrix to the reinforcement phase is 100:2-5.

2. A high-strength anchor bolt according to claim 1, characterized in that: The weight ratio of the sum of the weights of the Cu and the Se to the weight of the Sn is 1-3:

3.

3. A high-strength anchor bolt according to claim 2, characterized in that: The weight ratio of the Cu to the Se is 1:

1.

4. A high-strength anchor bolt according to claim 1, characterized in that: The median particle size of the boron nitride is 200nm~10μm.

5. The high-strength anchor bolt according to claim 1, characterized in that: The boron nitride is modified boron nitride, and the raw materials of the modified boron nitride include boron nitride, tungsten powder and molybdenum powder.

6. A high-strength anchor bolt according to claim 5, characterized in that: The weight ratio of the boron nitride, tungsten powder and molybdenum powder is 90:2-4:

1.

7. A high-strength anchor bolt according to claim 5, characterized in that: The preparation method of the modified boron nitride comprises the following steps: mixing the boron nitride, the tungsten powder and the molybdenum powder, hot pressing and sintering, and crushing to obtain the modified boron nitride.

8. A high-strength anchor bolt according to claim 7, characterized in that: During the hot pressing sintering, the temperature is 1500-1600° C., the pressure is 15-25 MPa, and the time is 2-3 hours.

9. A method for preparing a high-strength anchor bolt according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, weighing materials according to the weight percentage of the matrix components, mixing, and melting to obtain molten steel; S2, adding the reinforcing phase to the molten steel, mixing evenly, casting, and molding to obtain a bolt blank; S3, the bolt blank is drawn, cold-forged, threaded and heat-treated, and then cooled to obtain the anchor bolt.

10. The method for preparing a high-strength anchor bolt according to claim 9, characterized in that: In step S3, during the heat treatment, the temperature is 650-850° C. and the time is 1-2 hours.

Citation Information

Patent Citations

  • Drill rod

    CN107620342A

  • Steel for high-strength anti-seismic bracket as well as preparation method and application of steel

    CN119243044A

  • Abrasion resistance sintered body and method for producing same

    CN1847442A

  • Salt-resistant reinforcing bar for preventing deterioration of concrete

    JP1991020441A

  • Steel material having excellent alcohol corrosion resistance

    JP2014111807A